2019
DOI: 10.1021/acsomega.9b00566
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Internal Standards for Quantitative Matrix-Assisted Laser Desorption/Ionization Mass Spectrometric Analysis Based on Correlation Coefficients

Abstract: Matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) has shown its great success in the qualitative analysis of a wide range of organic and biological molecules. However, its application in quantitative analysis is still limited by the difficulty in the availability of isotope-labeled internal standards. The present work investigates the relationship between the correlation coefficient of the peak intensities of analyte and candidate internal standard ions and the linearity of possible quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This indicated that the S-CDs were composed of C, H and O atoms in the m/z range of 100 to 380, especially the pronounced peak at m/z 225 was observed. While the S-CDs conjugated with CP (CP@CDs-200) showed the mass-charge ratio (m/z) especially at 215, 248, 322 and 354, which revealed that CP was loaded onto the surface of S-CDs [ 56 ].
Figure 13.
…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the S-CDs were composed of C, H and O atoms in the m/z range of 100 to 380, especially the pronounced peak at m/z 225 was observed. While the S-CDs conjugated with CP (CP@CDs-200) showed the mass-charge ratio (m/z) especially at 215, 248, 322 and 354, which revealed that CP was loaded onto the surface of S-CDs [ 56 ].
Figure 13.
…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of PS and PET MNPs was further conducted using the internal standard method widely applied by an extensive list of published works. , Figure a illustrates the normalized signal intensities with variation in concentrations of LM-PS and LM-PET microplastics, which shows a nearly linear correlation ( R 2 = 0.90) between the signal intensity and concentration for PS but a nonlinear behavior for PET. When plotted as P normalization versus ln­[polymer concentration], the results in Figure b show that the data of both polymers fit a logarithmic regression with acceptable coefficients of determination ( R 2 > 0.96).…”
Section: Resultsmentioning
confidence: 99%